Demographic history and admixture dynamics in African Sahelian populations - Černý, Viktor; Fortes-Lima, Cesar; Tříska, Petr (Human molecular genetics, 2021)
The Sahel/Savannah belt of Africa is a contact zone between two subsistence systems (nomadic pastoralism and sedentary farming) and of two groups of populations, namely Eurasians penetrating from northern Africa southwards and sub-Saharan Africans migrating northwards. Because pastoralism is characterized by a high degree of mobility, it leaves few significant archaeological traces. Demographic history seen through the lens of population genetic studies complements our historical and archaeological knowledge in this African region. In this review, we highlight recent advances in our understanding of demographic history in the Sahel/Savannah belt as revealed by genetic studies. We show the impact of food-producing subsistence strategies on population structure and the somewhat different migration patterns in the western and eastern part of the region. Genomic studies show that the gene pool of various groups of Sahelians consists in a complex mosaic of several ancestries. We also touch upon various signals of genetic adaptations such as lactase persistence, taste sensitivity and malaria resistance, all of which have different distribution patterns among Sahelian populations. Overall, genetic studies contribute to gain a deeper understanding about the demographic and adaptive history of human populations in this specific African region and beyond.
Keywords: jižní Afrika; Human Migration; genový pool; DNA, Mitochondrial; lidé; Gene Pool; Genetics, Population; haplotypy; migrace lidstva; Haplotypes; Africa, Southern; černoši; populační genetika; mitochondriální DNA; Black People; zemědělství; Agriculture; Humans